Effects of Crushed and Powdered Brick Particles on Lightweight Papercrete - Tangbo, M. U.; Ibrahim, M. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2020)
This paper studied a light weight paper and mortar composite called papercrete which was produced using brick particles as aggregate and as pozzolan. Papercrete samples were produced with crushed brick particles to completely substitute sand as fine aggregate and labelled Sample BAP. Another set of samples were produced using crushed brick particles as aggregate and powdered brick particles as pozzolan to partially replace 10% of the cement content. These were labelled Sample BCP. Additional samples labelled Sample SP were produced with sand as aggregate and with no cement replacement to serve as controls. Initially, an X-ray diffraction analysis was performed on powdered brick particles to assess their chemical composition in line with ASTM 618. A total of 135 test samples were cast and tested for density, water absorption, compressive strength and tensile strength at 14 and 28 days. Similarly, samples were subjected to thermal conductivity and fire reaction tests. The results show an increase in density, compressive and tensile strength of Samples BAP and BCP over Sample SP. Additionally, all samples recorded low thermal conduction and a good reaction to fire as none of the samples ignited when subjected to fire. However, all samples had high water absorption values. It was concluded that using crushed and powdered brick particles to produce papercrete increases its density and strength and can be used as aggregate and pozzolan in producing papercrete.